STATE AND PROSPECTS OF MILK PROCESSING BRANCH IN LVIV REGION OF UKRAINE - Lesia Kobryn (Acta Scientiarum Polonorum. Oeconomia, 2013)
The results of milk processing branch in Lviv region of Ukraine under conditions of market and competitiveness are presented. The role of region's milk processing branch as well as the milk processing enterprises quantity dynamic and milk and dairy products production and consumption dynamic in region and its factors are shown. The regional products and producers milk and dairy products market structure as well as exportingimporting and innovative activity in milk processing branch are analyzed. The structure of milk processing enterprises raw materials base and possible perspective of regional milk processing branch are given.